The Circulating Concentration and 24-h Urine Excretion of Magnesium Dose- and Time-Dependently Respond to Oral Magnesium Supplementation in a Meta-Analysis of Randomized Controlled Trials. Issue 3 (10th February 2016) - Zhang, Xi; Del Gobbo, Liana C; Hruby, Adela; Rosanoff, Andrea; He, Ka; Dai, Qi; Costello, Rebecca B; Zhang, Wen; Song, Yiqing
Abstract: Background: Accurate determination of Mg status is important for improving nutritional assessment and clinical risk stratification. Objective: We aimed to quantify the overall responsiveness of Mg biomarkers to oral Mg supplementation among adults without severe diseases and their dose- and time responses using available data from randomized controlled trials (RCTs). Methods: We identified 48 Mg supplementation trials ( n = 2131) through searches of MEDLINE and the Cochrane Library up to November 2014. Random-effects meta-analysis was used to estimate weighted mean differences of biomarker concentrations between intervention and placebo groups. Restricted cubic splines were used to determine the dose- and time responses of Mg biomarkers to supplementation. Results: Among the 35 biomarkers assessed, serum, plasma, and urine Mg were most commonly measured. Elemental Mg supplementation doses ranged from 197 to 994 mg/d. Trials ranged from 3 wk to 5 y (median: 12 wk). Mg supplementation significantly elevated circulating Mg by 0.04 mmol/L (95% CI: 0.02, 0.06) and 24-h urine Mg excretion by 1.52 mmol/24 h (95% CI: 1.20, 1.83) as compared to placebo. Circulating Mg concentrations and 24-h urine Mg excretion responded to Mg supplementation in a dose- and time-dependent manner, gradually reaching a steady state at doses of 300 mg/d and 400 mg/d, or after 20 wk and 40 wk, respectively (all P -nonlinearity ≤ 0.001). The higher the circulating Mg concentration at baseline, the lower the responsiveness of circulating Mg to supplementation, and the higher the urinary excretion (all P -linearity < 0.05). In addition, RBC Mg, fecal Mg, and urine calcium were significantly more elevated by Mg supplementation than by placebo (all P- values < 0.05), but there is insufficient evidence to determine their responses to increasing Mg doses. Conclusions: This meta-analysis of RCTs demonstrated significant dose- and time responses of circulating Mg concentration and 24-h urine Mg excretion to oral Mg supplementation.